2005
DOI: 10.1007/s10551-005-1422-7
|View full text |Cite
|
Sign up to set email alerts
|

Sticks and Stones may Break Your Bones, but Words can Break Your Spirit: Bullying in the Workplace

Abstract: Workplace bullying has a well-established body of research internationally, but the United States has lagged behind the rest of the world in the identification and investigation of this phenomenon. This paper presents a managerial perspective on bullying in organizations. The lack of attention to the concept of workplace dignity in American organizational structures has supported and even encouraged both casual and more severe forms of harassment that our workplace laws do not currently cover. The demoralizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
107
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 172 publications
(115 citation statements)
references
References 13 publications
2
107
0
6
Order By: Relevance
“…Bullying in the workplace can also be declared as a form of psychological and domestic violence. Statistics have shown that it is three times more prevalent than sexual harassment (Namie, 2003) and involves deliberate humiliation of co-workers (Vega & Comer, 2005). Accordingly, Coyne, Seigne, and Randall (2000) declare bullying as a form of counterproductive behavior at work.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…Bullying in the workplace can also be declared as a form of psychological and domestic violence. Statistics have shown that it is three times more prevalent than sexual harassment (Namie, 2003) and involves deliberate humiliation of co-workers (Vega & Comer, 2005). Accordingly, Coyne, Seigne, and Randall (2000) declare bullying as a form of counterproductive behavior at work.…”
Section: Literature Reviewmentioning
confidence: 99%
“…However, bullying does not refer to harmless incivility and teasing (Vega & Comer, 2005). Speaking on the same lines, Yamada (2008) argues that a custom disagreement with a tough boss, having a difficult task to accomplish, or mere disagreements on job does not signify bullying behaviors.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Offline harassment has a well-established body of business ethics research that includes racial harassment (e.g., Stevens, 2001), sexual harassment (e.g., Baugh, 1997;Bell et al, 2002;Wells and Kracher, 1993), and work victimization (e.g., Vega and Comer, 2005;Wornham, 2003), but the identification and investigation of cyber harassment and cyber stalking (i.e., repeated cyber harassment over a period of time) is an under-exposed research theme. In contrast, cyber harassment receives considerably more attention in the popular press.…”
Section: Justice Perceptions Of Decisions To Intervene Across Identitmentioning
confidence: 99%